2021
DOI: 10.1186/s12891-021-04625-7
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia due to intradural cement leakage after vertebroplasty: a case report and literature review

Abstract: Background Vertebroplasty (VP) is considered an alternative therapy in an osteoporotic compression fracture that failed conservative treatment. However, cement leakage into the intradural space can cause catastrophic complications. To the best of our knowledge, intradural cement leakage following VP has been reported only in 7 cases. We report here a case of intradural cement leakage following VP with a literature review. Case presentation An 84-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Limited data in the literature on cases operated in the later period. [ 7 , 8 ] In our case, the operation was performed after a very long period (3 rd month) with the posterior hemilaminectomy approach, thus avoiding instability and the need for stabilization. However, there is also a chance that the patient may develop delayed kyphosis despite the minimally invasive approach that was taken.…”
Section: Discussionmentioning
confidence: 96%
“…Limited data in the literature on cases operated in the later period. [ 7 , 8 ] In our case, the operation was performed after a very long period (3 rd month) with the posterior hemilaminectomy approach, thus avoiding instability and the need for stabilization. However, there is also a chance that the patient may develop delayed kyphosis despite the minimally invasive approach that was taken.…”
Section: Discussionmentioning
confidence: 96%
“…At the same time, excessive bone cement infusion can result in leakage events. In severe instances, the bone cement entering the spinal canal might compress nerve tissue, potentially causing paralysis in the patient (27). Therefore, an appropriate proportion of cement infusion in PKP can yield good patient outcomes and reduce the incidence of clinical adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported in their meta-analysis that symptomatic cement leakage occurs in 1.08% [ 79 ]. Complications associated with bone cement leakage include pulmonary cement embolism [ 62 , 69 , 88 ], cardiac cement embolism [ 63 , 70 ], bilateral lower limb paraplegia due to intravertebral canal cement leakage [ 55 , 59 , 89 , 90 ], and a cement-embolic cerebral infarction [ 84 ], which are described below.…”
Section: Potential Risk Of Pvp Procedures For Osteoporotic Vertebral ...mentioning
confidence: 99%
“…To prevent these complications, penetration of the inside of the pedicle should be avoided, and the viscosity of the PMMA must be monitored. Immediate spinal canal decompression surgery is recommended when paraplegia is due to a space-occupying lesion in the spinal canal [ 59 61 , 89 , 90 , 94 ].…”
Section: Potential Risk Of Pvp Procedures For Osteoporotic Vertebral ...mentioning
confidence: 99%